Contrasting roles of fungal and oomycete pathogens in mediating nitrogen addition and winter grazing effects on biomass - Peng Zhang; Mengjiao Huang; Chaorui Chen; Kui Hu; Junsheng Ke; Mu Liu; Yao Xiao; Xiang Liu (Ecology, 2024)
Both bottom‐up and top‐down processes modulate plant communities. Fungal and oomycete pathogens are most common in global grasslands, and due to differences in their physiology, function, host range, and life cycles, they may differentially affect plants (in both intensity and direction). However, how fungal and oomycete pathogens regulate bottom‐up and top‐down effects on plant community biomass remains unclear. To this end, we conducted a 3‐year field experiment in an alpine meadow incorporating mammalian herbivore exclosure, fungicide/oomyceticide application, and nitrogen addition treatments. We arranged 12 blocks with half randomly assigned to be mammalian herbivore exclosures (fenced to exclude grazing sheep), and the other half were fenced most of the year but not in winter (winter grazing control). Six 2.5 × 2.5 m square plots were established in each block, with each of the six plots assigned as control, nitrogen addition, fungicide application, oomyceticide application, nitrogen addition + fungicide application, and nitrogen addition + oomyceticide application. We found that fungicide application significantly increased plant community biomass (mainly Poaceae species) under nitrogen addition and promoted the bottom‐up effect of nitrogen addition on plant community biomass by altering the community‐weighted mean of plant height (via species turnover). Meanwhile, oomyceticide application significantly increased plant community biomass (mainly Poaceae species) when mammalian herbivores were excluded and weakened the top‐down effect of winter grazing on plant community biomass by driving intraspecific variation in plant height. Our results highlight that fungal and oomycete pathogens play important (but differing) roles in mediating the effects of nutrient availability and higher trophic levels on plant community biomass. Mechanistically, we demonstrated that plant pathogen‐related modulation of plant community biomass is achieved by alterations to plant height. Overall, this study combines both community and disease ecology to reveal complex interactions among higher trophic levels and their potential impacts on terrestrial ecosystem functioning under human disturbance.